Primary Angiitis of the Central Nervous System: A Report of Three Cases from a Single Colombian Center - Nicolás Coronel-Restrepo; Fabio Bonilla-Abadía; Omar A. Cortes; Jorge H. Izquierdo; Alberto M. Shinchi; Juan C. Bravo; Gabriel J. Tobón; Carlos A. Cañas (Case Reports in Neurological Medicine)
The primary angiitis of the central nervous system (PACNS) is an entity with a very low incidence and prevalence. It is not clear why the inflammatory process of this entity is limited to the cerebral vasculature without systemic manifestations. Its clinical manifestations are very heterogeneous and make clinical diagnosis difficult. In most cases, a brain biopsy is required. Only the clinical suspicion and the ability to recognize the possible clinical and imagenological patterns of presentation make an accurate diagnosis possible. The vast majority of the treatment recommendations are given by series of case reports. The following paper described the clinical, imagenological, and histopathological characteristics of three Colombian patients with PACNS. The strategic therapeutic used in shown.